Pure red cell aplasia among ABO mismatched hematopoietic stem cell transplant recipients: a 13-years retrospective study and literature review - Metafuni, Elisabetta; Busnego Barreto, Maria Teresa; Valentini, Caterina Giovanna; Giammarco, Sabrina; Limongiello, Maria Assunta; Sorà, Federica; Bianchi, Maria; Massini, Giuseppina; Piccirillo, Nicola; Putzulu, Rossana; Frioni, Filippo; Bacigalupo, Andrea; et al. (Frontiers in Oncology, 2024)
Background Pure red cell aplasia (PRCA) is a possible complication after allogeneic hematopoietic stem cell transplantation (HSCT) with major ABO incompatibility. Patients experience delayed engraftment of the erythroid series, with prolonged transfusion-dependent anemia and iron overload. Methods We performed a revision of the most recent literature about post-HSCT PRCA treatment procedures. Moreover, we conducted a retrospective study, over the last 13-years, which included all consecutive major ABO mismatched HSCT performed in our unit, with the aim to assess PRCA incidence, risk factors, and response to different treatments. Overall, 194 patients received a major ABO mismatched transplant from 2010 to 2022. For each patient, data about demographic and transplant characteristics, engraftment, blood transfusion, and possible treatment received were collected. Results The literature review returned 23 eligible papers on PRCA treatment, with high success rate using plasma-exchange (PEX) and immunoadsorption procedures, daratumumab, and eltrombopag. Our study identified a total of 24 cases of PRCA. Among risk factors for PRCA development, we have found older recipient age (p=0.01), high pre-HSCT IgG and IgM IHA titer (p<0.0001), major rather than bidirectional ABO incompatibility (p=0.02), low T CD8 lymphocyte count in the graft (p=0.006), relative donor (p=0.02) and bone marrow as stem cell source (p=0.002). However, multivariate analysis confirmed only pre-HSCT IgG IHA titer as the unique risk factor for PRCA occurrence. The optimal cut-off value of pre-HSCT IgG IHA for PRCA development, resulted to be 1/64, with a 100% sensitivity and 68.8% specificity (p<0.0001). All patients with PRCA had received rhEPO and transfusion support and 20 patients received additional treatments like PEX, rituximab, and more recently daratumumab. Comprehensively, PEX and rituximab obtained a response in half of the cases, at a variable time, while the few cases of patients we treated with daratumumab suggest promising results. The overall response rate in our cohort was 75%, with significantly better survival (94.4% vs. 16.7%) and lower transplant-related mortality (6.3% vs. 80%) for PRCA responders. Conclusions Standardized guidelines on when and how to treat PRCA are necessary because the current treatment is controversial among centers.